2015
DOI: 10.1007/s10120-015-0465-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of lymphatic involvement in differentiated-type intramucosal gastric cancers as examined by endoscopic resection

Abstract: Background Lymphatic involvement may sometimes be detected in differentiated-type intramucosal cancer resected endoscopically during routine examination, but its incidence and clinical significance remain unknown. Methods We examined 300 endoscopically resected lesions obtained from 238 patients diagnosed with differentiated-type intramucosal gastric cancer. All sections were subjected to D2-40 monoclonal-based immunohistochemistry. Results The incidence of lymphatic involvement in differentiated-type intramuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Regarding the prognosis of non-curative ESD cases, there are several previous studies comparing additional surgical procedure cases with follow-up cases [6, 7, 10-12]. Hoteya et al [11] reported that no LNM was observed in MGC in either group, and there was no difference in the survival rate between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the prognosis of non-curative ESD cases, there are several previous studies comparing additional surgical procedure cases with follow-up cases [6, 7, 10-12]. Hoteya et al [11] reported that no LNM was observed in MGC in either group, and there was no difference in the survival rate between the 2 groups.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding MGCs with LVI, Fujita et al [7] reported 6 Ly-positive cases (2.0%) among 300 differentiated MGCs resected by ESD. After ESD, neither the 3 cases that underwent additional surgery, nor the 3 cases with follow-up reported LNM.…”
Section: Introductionmentioning
confidence: 99%
“…Diffuse or focal expression of any one of the three primitive markers was regarded as positive for primitive phenotype. D2–40 is a marker for lymphatic vessels, and cancer cells were confirmed to have lymphatic invasion if D2–40-positive cells surrounded the lumen [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…After scanning titles and abstracts, 47 citations remained for full-text assessment. The search results and selection process are summarized in Fig 1 . Twenty-three studies were excluded for the following reasons: 9 studies did not include histological mixed-type classification [16,[26][27][28][29][30][31][32][33]; 6 did not directly mention the number of LNM cases [34][35][36][37][38][39]; 3 were considered to have unreliable data [40][41][42]; 2 were not confined to EGC [12,43]; and 3 were not accessible online. Finally, 24 studies were deemed eligible for the meta-analysis.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%